Analisis Ergonomi Lingkungan Fisik Bengkel Kerja Program Keahlian Teknik Permesinan SMK di Kota Makassar - Baharuddin, Fiskia Rera; Palerangi, Andi Muadz (Universitas Negeri Makassar, 2017)
Ergonomic physical environment workshop is one of the supporting factors in the process of vocational learning, especially the practicum. The main problems in this activity are the ergonomic conditions of the physical environment workshop is less conducive thermal comfort aspects, minimal lighting, disturbing noise, and poorly designed workspace such as oil fluid and equipment scattered on the floor. This condition can lead to fatigue, negligence and accidents, which will affect the development and improvement of students’ competence. The purpose of this study is to know the description and information about ergonomic standard of ideal physical environment including thermal, lighting, acoustic (noise), and work room design. This study is a quantitative approach with survey method. The technique of collecting data uses observation and direct measurement. The result of descriptive analysis and conclusion shows that; (1) the thermal comfort is at 32.10 °C, while the ideal standard ranges from 24 °C-27 °C; (2) llighting with a value of 460.26 Lux while the ideal standard ranges from 200 to 300 Lux; (3) the illusion (noise) with a value of 80.97 dB, while the ideal standard for space theory ranges between 35-45 dB and practical space of 85 dB, and: (4) spatial design with 46.21 m2 results, while the standard ideal size for each work unit ranges from 64 m2. Keywords: ergonomic, physical environment, workshop